Dieta hiperproteica com treinamento multicomponente na perda de peso e perfil lipídico de mulheres em pós-menopausa - Reinaldo, Jamille Mendonça (2018)
INTRODUCTION: Aging changes occur early in women due to changes in sex hormones that occur during the climacteric, such as reduced strength and muscle mass in addition to increased adiposity. The high protein diet with caloric restriction combined with resistance training has shown positive effects against these changes. However it must be investigated what happens when combined with the multicomponent exercise. OBJECTIVE: To evaluate the effect of high protein diet associated with multicomponent training on body mass reduction and biochemical markers in postmenopausal women. METHODOLOGY: The intervention lasted 12 weeks and participated in this study 41 women in postmenopausal (> 12 months of amenorrhea) residents in the municipalities of São Cristóvão and Aracaju. The average age of the sample was 65.6 ± 5.2 years. The participants have integrated a program that combined the low-calorie dietary prescription and multicomponent training. The women were randomly assigned to the High protein diet (HP), which presented protein intake> 20% total energy value (~ 1.2g / kg / day) and Control group (C) with the normal protein diet (~0.9 g / kg / day), both with caloric restriction of ~ 500 kcal / day and 600 kcal / day respectively. Multicomponent training occurred 3 times a week non-consecutive days with duration of 60 minutes each session. The statistical analyses were conducted by the software SPSS version 20 and applied the 2x2 ANOVA with Bonferroni post hoc. It was considered significant p values < 0.05. RESULTS: The study concluded those 29 women, 16 of the HP group and 13 of the C group. Body mass (F (1.27) = 8.24, p <0.05) and hip circumference (F (1.27) = 15.55, p <0.01) decreased in the HP group and calf circumference (F (1.27) = 6.85 p = 0.01) in the C group. High-density lipoprotein increased while low-density lipoprotein, total cholesterol and triglycerides were reduced in the HP group (p <0.05). Fasting glycaemia was reduced and physical fitness increased in both groups (p <0.05). CONCLUSION: HP diet combined with multicomponent training showed weight loss with maintenance of muscle mass and contributed to the improvement of the lipid profile in postmenopausal women. Both HP and C presented positive changes in fasting and physical fitness glycaemia.